Diazotroph-Derived Nitrogen Assimilation Strategies Differ by Scleractinian Coral Species - Meunier, Valentine; Bonnet, Sophie; Benavides, Mar; Ravache, Andreas; Grosso, Olivier; Lambert, Christophe; Houlbrèque, Fanny (Frontiers in Marine Science, 2021)
Reef-building corals generally thrive in nutrient-poor tropical waters, where among other elements, nitrogen (N) availability often limits primary productivity. In addition to their close association with endosymbiotic dinoflagellates of the family Symbiodiniaceae, enabling an effective use and retention of dissolved inorganic nitrogen (DIN), scleractinian corals have developed strategies to acquire new N: (1) They can ingest N-rich sediment particles and preys (from picoplankton to macro-zooplankton) via heterotrophy, including diazotrophs [plankton fixing dinitrogen (N2) and releasing part of this nitrogen—Diazotroph-Derived N (DDN)—in seawater], a pathway called “heterotrophic nutrition on diazotrophs”; (2) Symbiotic diazotrophs located in the coral holobiont have the molecular machinery to fix N2, a pathway called “symbiotic N2 fixation”. Here we used the 15N2 isotopic labeling in a series of incubations to investigate the relative contribution of each of these DDN transfer pathways in three worldwide distributed coral species: Acropora muricata, Galaxea fascicularis, and Pocillopora damicornis. We show that N provision via “symbiotic N2 fixation” is negligible compared to that obtained via “heterotrophic nutrition on diazotrophs,” with DDN assimilation rates about a thousand times lower for P. damicornis and G. fascicularis, or assimilation rates via “symbiotic N2 fixation” almost nil for A. muricata. Through heterotrophic feeding on planktonic diazotrophs, only G. fascicularis and P. damicornis can successfully obtain N and fulfill a large part of their N requirements (DDN asimilation rates: 0.111 ± 0.056 and 0.517 ± 0.070 μg N cm–2 h–1 in their Symbiodiniaceae, respectively). Whereas this contribution is again negligible for A. muricata. They also largely consume the picoplankton that likely benefit from this DDN (Prochlorococcus and Synechococcus cells; respectively, 2.56 ± 1.57 104 and 2.70 ± 1.66 104 cell h–1 cm–2 for G. fascicularis; 3.02 ± 0.19 105 and 1.14 ± 0.79 104 cell h–1 cm–2 for P. damicornis). The present study confirms the different dependencies of the three tested species regarding heterotrophy, with P. damicornis and G. fascicularis appearing highly efficient at capturing plankton, while A. muricata, considered as mainly autotroph, does not rely on these food resources to meet its N and energy needs.